Temperament and psychopathology in early childhood predict body dissatisfaction and eating disorder symptoms in adolescence. (April 2022) - Bufferd, Sara J.; Levinson, Cheri A.; Olino, Thomas M.; Dougherty, Lea R.; Dyson, Margaret W.; Carlson, Gabrielle A.; Klein, Daniel N.
Abstract: Eating disorders (ED) are highly impairing and dangerous conditions that typically onset in adolescence. However, very few prospective studies have examined early childhood risk factors for ED pathology. Given well-established links between temperament and psychopathology, examination of these factors could inform prevention efforts. The current multi-method, multi-informant prospective longitudinal study tested whether laboratory-observed and parent-reported temperament and psychiatric disorders at ages 3 and 6 ( N = 609) predict body dissatisfaction at ages 12 and 15 and dimensional symptoms of EDs (anorexia nervosa [AN] and bulimia nervosa [BN]) at age 15 ( n = 458) in a community sample. Results indicated that early childhood temperament (positive and negative emotionality, perceptual sensitivity, impulsivity, less shyness) and childhood psychopathology (anxiety, oppositional defiant, attention deficit/hyperactivity, and depressive disorders), predicted body dissatisfaction in adolescence. In addition, childhood perceptual sensitivity and oppositional defiant and depressive disorders predicted AN symptoms. Demographic characteristics (female sex, lower levels of fathers' education, and parental marital status) in childhood predicted body dissatisfaction and AN symptoms. No temperament or psychopathology variables predicted BN symptoms. This study is an important first step toward continuing to identify areas of focus for future research on early childhood risk factors for ED symptoms and body dissatisfaction. Highlights: We examined early childhood predictors of body dissatisfaction and ED symptoms. Child temperament and psychopathology predict body dissatisfaction and AN symptoms. Child NE, shyness, anxiety, and ODD predict body dissatisfaction. Child perceptual sensitivity, depression and ODD predict AN symptoms. Female sex and less paternal education predict body dissatisfaction and AN symptoms.